Human capital management: new factors of production in the Indonesian life insurance industry - Suhardi, Suhardi; Wasiman, Wasiman; Soemadijo, Pramita Studiviany; Wangdra, Yvonne; Purwati, Titik (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In the current era of the Information Society, competition in any business industry is increasingly fierce. However, the lack of skilled workers is a major obstacle in increasing company production. Human Resources problems are still not enough to overcome complex problems. In the current era of modern globalization, competitive advantage is largely determined by the formation of Human Capital. The inadequate level of knowledge from theoretical and practical aspects of Human Capital Management in increasing sustainable production determines the objectives of this research and problem formulation so that solutions can be found, because the attention of developed and developing countries is currently more focused on developing Human Capital which is one of the company's solutions in Human Resources development which tends to have a significant impact on performance. This research examines Human Capital's direct impact on employee performance and becomes a new production factor in the Indonesian Life Insurance industry. The results of this research are to justify and develop that human capital management including TASK (Talent, Attitude, Skill, Knowledge) through continuous training with studies in the Indonesian Life Insurance Industry sector is a production factor that can also improve employee and company performance.